STUDI HADIS-HADIS TENTANG SHALAT JENAZAH - Fredika Ramadanil (UIN Imam Bonjol Padang, 2018)
Islamic funeral prayer or “Janaza prayer” is a collective obligation upon Muslims as a part of the Islamic funeral ritual. The prayer is performed in congregation to seek pardon for the deceased and all dead Muslims. As with any religion, Islam has funeral customs and its different practices among the Muslims to guide the bereaved. However, certain steps must be followed, including washing and shrouding the body, funeral prayers at the mosque and so on. This study was conducted with the purpose of determining who is the most worthy person to lead a funeral prayer and clarifying the Prophetic traditons on the hadith said that the Prophet of Allah refused to lead the funeral prayer that be held for those who were known to be corruptor and adulterers, where it apparently caused polemics among the majority of jurists today. The library research was conducted by gathering data from sources of bibliography related to the topic. Hence, this study expects to give a clear and concise explanation regarding the hadith understanding of the funeral prayer in which more focused to the traditions on ‘who is the most worthy person to lead a funeral prayer’ and the hadith said that ‘the Prophet of Allah refused to lead the funeral prayer that be held for those who were known to be corruptor and adulterers.